1991
DOI: 10.1128/jb.173.23.7449-7457.1991
|View full text |Cite
|
Sign up to set email alerts
|

Copper-zinc superoxide dismutase of Haemophilus influenzae and H. parainfluenzae

Abstract: Copper-zinc superoxide dismutase ([Cu,Zn]-SOD) is widely found in eukaryotes but has only rarely been identified in bacteria. Here we describe sodC, encoding [Cu,Zn]-SOD in Haemophilus influenzae and H. parainfluenzae, frequent colonists and pathogens of the human respiratory tract. In capsulate H. influenzae, sodC was found in only one division of the bacterial population, and although the protein it encoded was clearly [Cu,Zn]-SOD from its deduced sequence, it lacked enzymatic activity. In H. parainfluenzae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
116
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 50 publications
0
116
0
Order By: Relevance
“…SODs are classified according to the metalloenzyme at their active site. Copper, zinc (Cu,Zn) cofactored SODs were originally thought to be restricted to eukaryotes but have recently been shown to be present in many Gram-negative pathogens, including Brucella abortus (Beck et al, 1990), members of the Haemophilus-Actinobacillus-Pasteurella group, Neisseria meningitidis (Kroll et al, 1991; Escherichia coli (Benov and Fridovich, 1994) and Legionella pneumophila (St John and Steinman, 1996). We have recently shown that Salmonella possesses a [Cu,Zn]-SOD (Canvin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…SODs are classified according to the metalloenzyme at their active site. Copper, zinc (Cu,Zn) cofactored SODs were originally thought to be restricted to eukaryotes but have recently been shown to be present in many Gram-negative pathogens, including Brucella abortus (Beck et al, 1990), members of the Haemophilus-Actinobacillus-Pasteurella group, Neisseria meningitidis (Kroll et al, 1991; Escherichia coli (Benov and Fridovich, 1994) and Legionella pneumophila (St John and Steinman, 1996). We have recently shown that Salmonella possesses a [Cu,Zn]-SOD (Canvin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In extensive studies, we have established that capsulated or noncapsulated H. influenzae sensu stricto strains do not produce active CuZnSOD (11,12,14,16). The population of capsulated H. influenzae strains falls into two widely separated phylogenetic divisions, and while strains segregating to phylogenetic division II (some serotype a and b strains and serotype f strains) plus serotype e strains (distantly related to phylogenetic division II) possess the sodC gene, they do not produce active enzyme (11,16), probably due to a mutation that converts an active-site histidine to tyrosine (11). Among a collection of 45 NT H. influenzae isolates (20), characterized by multilocus enzyme electrophoresis, comprising electrophoretic types 11 to 13, 26 to 27, 29 to 32, 35 to 45, 49 to 51, 53 to 55, 57 to 61, and 63 to 76, neither the sodC gene nor the CuZnSOD protein was detected (16).…”
Section: Infection With Nontypeable (Nt)mentioning
confidence: 99%
“…Bacterial CuZnSODs are enzymes found in the periplasms of various gram-negative bacteria and, in the case of pathogens, are thought to have a role in the protection of organisms against host defense-derived free-radical-mediated damage (1,2,6,11,12,15,27). In extensive studies, we have established that capsulated or noncapsulated H. influenzae sensu stricto strains do not produce active CuZnSOD (11,12,14,16).…”
Section: Infection With Nontypeable (Nt)mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing number of structurally characterized prokaryotic Cu,Zn superoxide dismutases show a considerable structural variability between proteins from different bacteria, therefore individual enzyme variants may exhibit unique properties [3][4][5][6][7][8]. Such species-specific differences include alteration in the quaternary structure [3,4], mutations in the active site ligands [5][6][7], deletion or insertion in the major enzyme loops [6,7], or the introduction of additional domains at the N-or C-terminus of the enzyme [8]. The Cu,Zn SODs from a few Gram-negative bacteria possess histidine-rich N-terminal extensions, which show typical features of high affinity divalent metal binding domains [8].…”
Section: Introductionmentioning
confidence: 99%